Enumerating Hamiltonian Cycles in a Planar Graph Using Combinatorial Cycle Bases - Retno MAHARESI (Journal of Applied Computer Science & Mathematics, 2016)
Cycle bases belong to a k-connected simple graph used both for listing and enumerating Hamiltonian cycles contained in a planar graph. Planar cycle bases have a weighted induced graph whose weight values limited to 1. Hence making it was possible used in the Hamiltonian cycle enumeration procedures efficiently. In this paper a Hamiltonian cycle enumeration scheme is obtained through two stages. First, i cycles out of m bases cycles are determined using an appropriate constructed constraint. Secondly, to search all Hamiltonian cycles which are formed by the combination of i bases cycles obtained in the first stage efficiently. This efficiency achieved through a generation a class of objects as the representation of i cycle combinations among m bases cycles. The experiment conducted based on the proposed algorithm successfully generated and enumerated all the Hamiltonian cycles contained in a well-known example of planar graph.